O3-S6.05 Perceptions on point-of-care tests for sexually transmitted infections‑disconnect between frontline clinicians and professionals in industry. (10th July 2011) - Hsieh, Yu-Hsiang; Gaydos, C; Hogan, T; Uy, O; Jackman, J; Jett-Goheen, Mary; Rompalo, A
Abstract : Background: Some recently developed or available sexually transmitted infection (STI) point-of-care tests (POCTs) are not very accurate and are not feasible for use in clinical settings. We conducted a study to determine if a gap exists between STI clinicians/academic experts and industry professionals regarding perceptions of the ideal types and characteristics of STI POCTs. Methods: Our online survey design informed by a large-scale focus group study among STI professionals contained sections on demographics; barriers of use for available STI POCTs; characteristics of an ideal POCT, including prioritising pathogens for targets; and building your own POCT". Practicing clinicians and academic experts from two venues, STI-related international conference attendees and U.S. STD clinic clinicians, were invited to participate in the clinician survey. Professionals from industry in the STI diagnostic field were invited to participate in the industry survey. χ 2 test and conditional logistical regression were used for data analysis. Results: Clinician survey participants (n=218) identified "the time frame required" (39.9%), "complexity" (31.2%), and "interruption of work flow" (30.3%) as the top three barriers making it difficult to use STI POCTs, while the industry survey participants (n=107) identified "complexity" (65.4%), "unreliability" (53.3%), and "difficulty in reading results" (34.6%) as the top three barriers. Significant differences in barriers named in the two surveys included "complexity", "the time frame required", "laboratory driven", "difficulty in reading results", and "unreliability". Participants from both surveys ranked C trachomatis as the top priority organism chosen for a new POCT (clinician: 62%, industry: 39%, p<0.05), followed by a test that would diagnose early seroconversion for HIV (clinician: 14%, industry: 32%, p<0.05). Sensitivity was always the most important attribute to be considered for a new STI POCT by both participant groups. Participants of the clinician group chose cost as the second priority attribute, while those of the industry group chose specificity as the second priority. Conclusions: We identified differences in the perceptions regarding barriers and ideal attributes for STI POCTs between frontline clinical providers and industry personnel. Tailored training is warranted to inform scientists, biomedical engineers, and other industry experts about characteristics that clinicians desire for STI POCTs.